A Rare Case of Carotid Web Presenting with Ischemic Stroke in a Young Woman and a Brief Review of the Literature - Kyaw Kyaw; Htun Latt; Sammy San Myint Aung; Jay Babu; Rajesh Rangaswamy (Case Reports in Medicine)
Carotid web is a radiological description of a shelf-like intraluminal filling defect in the carotid bulb. It is histologically defined as atypical fibromuscular dysplasia (FMD), with abnormal fibrosis and smooth muscle cell hyperplasia in the tunica intima. The spur-like intraluminal protrusion can serve as a nidus for thrombus formation, which could cause systemic embolism and ischemic strokes. We report a case of a 20-year-old female patient presenting with acute ischemic stroke in the ipsilateral middle cerebral artery (MCA) territory. We also discuss the incidence, the prevalence, the pathophysiology, the treatment, and the recurrence of carotid web based on the currently available literature.